A Modern Business Management Approach to Growth Company in the Context of Sustainable Strategy - Yulianti, Sri; Nuraini, Ani; Supriyani, Mei (Lembaga Layanan Pendidikan Tinggi Wilayah III DKI Jakarta, 2025)
This research examines the implementation of modern business management approaches in driving corporate growth in the context of sustainability strategies. Using mixed methods that combine quantitative and qualitative analysis, this study examines how sustainability strategies are integrated into the business models of companies in Indonesia. Modern business management demands the integration of sustainability aspects in corporate strategy. This research discusses the concept, implementation, and benefits of business management as well as sustainable strategies that work in the business field, highlighting the importance of balance between economic growth, social responsibility, and environmental management. Data was obtained from 120 medium and large companies operating in various industrial sectors during the period 2020-2024. The results show that companies that adopt sustainable business practices, sustainable management strategies are able to increase their competitive advantage, reputation, and resilience in the face of global challenges. The findings of this study are that the implementation of sustainable strategies with a holistic approach in modern business management that integrates economic value with social and environmental values so as to improve operational efficiency, strengthen brands, increase competitiveness, and create corporate resilience, showing better revenue growth and profitability in the long run. This research contributes to a better understanding of how companies can achieve sustainable growth in a dynamic business environment.